Movências tamacheque além-fronteiras: conexões, performances em narrativas insurgentes em festivais culturais saarianos (2001-2017) - Adnane, Mahfouz Ag (2019)
This study deals with movences of expressive tamacheque practices, coming out from the ishumar music or the teshumara cultural movement, in Saharan circuits, established in the last decades. Musicality, orality, visuality, performances and cultural history - present in the festivals, intercommunal meetings and other performances in the urban environment - refer to the problematic Sahara and Sael fragmentation by territorial, cultural and aesthetic borders. The research, focused on the period between 2001 and 2017, is based on a survey and documentary analysis (publications, catalogs of events, websites, official documents) and field research in Mali and Morocco - held in 2016 and 2017. The focus is on the constitution of sources based on the dynamics of orality, with interviews and observations at festivals, various musical encounters, urban cultural spaces and dialogue with artists, producers, cultural agents and festivals. In the context of processes that gave geopolitical and territorial form to the current national states of West and North Africa, there was denial and negligence of their plural cultural composition. In the Malian situation, there were also several actions by the tamacheque society, both with a view to socio-cultural recognition and self-determination through arms. After peace agreements of armed conflict (1990-1996) between Tamacheque society and the central governments of Mali and Niger, various artists and cultural agents organized festivals and intercommunal meetings, valuing their presence in the Sahara and the Sahel. Contemporary festivals rely on artistic expressions and on the ethical, political and aesthetic manifestations of intercommunal encounters such as tamakanit or takubelt. The contemporary mobility of tamacheque society includes the Saharan movements, interconnecting spatialities is a factor of impact both in the cultural scene of capitals and large cities as in the annual meetings of the nomadic life and in the local festivities. The plasticity of identities and the mix of aesthetic languages and expressions provide a broadening of horizons and dialogues in order to make possible the historical and cultural march of the societies of and in the Sahara, among them the tamacheque